2015
DOI: 10.1016/j.jjcc.2014.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Relation between stent thrombosis and calcium channel blocker after drug-eluting stent implantation

Abstract: These results suggest that CCB use may be associated with a decreased risk of ST after DES implantation within 1 year in Japanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A Japanese registry including DES-treated patients (n ¼ 3,493) showed that CCB use was significantly lower in patients with versus without stent thrombosis (25.0% vs. 51.4%; p ¼ 0.016). 27 In multiple regression analysis, the CCB use was a major negative predictor for the risk of stent thrombosis within 1 year (OR: 0.209; 95% CI: 0.045-0.973; p ¼ 0.046). A Taiwan registry including PCI-treated ACS patients (n ¼ 51,925) assessed the potential modification effect according to the compliance with clopidogrel.…”
Section: Discussionmentioning
confidence: 95%
“…A Japanese registry including DES-treated patients (n ¼ 3,493) showed that CCB use was significantly lower in patients with versus without stent thrombosis (25.0% vs. 51.4%; p ¼ 0.016). 27 In multiple regression analysis, the CCB use was a major negative predictor for the risk of stent thrombosis within 1 year (OR: 0.209; 95% CI: 0.045-0.973; p ¼ 0.046). A Taiwan registry including PCI-treated ACS patients (n ¼ 51,925) assessed the potential modification effect according to the compliance with clopidogrel.…”
Section: Discussionmentioning
confidence: 95%
“…Other DHB-CCBs, namely amlodipine and felodipine, also exerted non-significant protection, which suggests a potential group effect. Calcium ions are the major regulators of coagulation cascade, and previous evidence suggests that CCBs may have a protective association with stent thrombosis in coronary artery disease, 45 and vice versa, may potentiate the risk of GI bleeding in hypertensive patients. 46 However, the relationship between DHP CCBs and VTE has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that compared with placebo, patients receiving CCB treatment had signi cantly reduced incidence of restenosis and clinical events. Nagano M et al [22] in a Japanese KICS study found that the use of CCB may be associated with a reduced risk of Stent thrombosis(ST) within 1 year after drug-eluting stent (DES) placement. The 2019 European Guidelines for the Diagnosis and Management of Chronic Coronary Syndrome also advocate the use of CCB for initial treatment [23] .…”
Section: Introductionmentioning
confidence: 99%